(untitled) - Gul, S. (New York, 1998)
This book summarizes the key principles underlying enzyme assays, including assay design and the evaluation of experimental data. It provides details of and references to the major physico–chemical techniques commonly used in enzymology. Useful ancillary data are also included on subjects such as active site titration, reagent kits and buffers. The Essential Data series provides rapid access to the core data required by researchers on a daily basis, in convenient pocket–sized volumes.
Keywords: Enzymes,Enzym; Analysis,Phân tích